Core Outcome Set for Trials Aimed at Improving the Appropriateness of Polypharmacy in Older People in Primary Care. Issue 6 (20th February 2018) - Rankin, Audrey; Cadogan, Cathal A.; ın Ryan, Crist_; Clyne, Barbara; Smith, Susan M.; Hughes, Carmel M.
Abstract : OBJECTIVES: To develop a core outcome set (COS) for use in effectiveness trials of interventions aiming to improve the appropriateness of polypharmacy in older people in primary care. DESIGN: Standard COS development methodology was followed, comprising identification of outcomes of studies from an update of a Cochrane systematic review and previously collected qualitative data and an online Delphi consensus exercise involving three rounds. PARTICIPANTS: An international panel of 160 stakeholders comprising 120 healthcare experts and a public participant panel of 40 older people. MEASUREMENTS: Outcomes identified from studies included in the Cochrane review and secondary analysis of previously collected qualitative data were scored on a 9‐point Likert scale using the GRADE scoring system anchored at 1 (not important) and 9 (critical). Consensus criteria for the COS were defined as 70% or more of participants scoring the outcome as critical and 15% or fewer scoring the outcome as not important. RESULTS: Twenty‐nine outcomes identified from the Cochrane review and existing qualitative data were included in the Delphi exercise. The final COS comprised 16 outcomes. The 7 highest‐ranked outcomes were serious adverse drug reactions, medication appropriateness, falls, medication regimen complexity, quality of life, mortality, and medication side effects. CONCLUSION: A COS for interventions aiming to improve the appropriateness of polypharmacy for older people in primary care has been developed. Future work will focus on identifying appropriate tools to measure Abstract : See related editorial byZachary A. Marcum .